FA’ĀLIYAH WASĪLAH AL-KALIMĀT AL-MUTAQĀṬI‘AH LI SAIṬARAH AT-ṬULLĀB ‘ALA FAHM AN-NAṢ AL-‘ARABI FĪ SMP IT MADRASAHATUL QUR’AN ACEH BESAR - Mukhlisah, Mukhlisah; Nurrahmi, Nurrahmi; Adhim, Said Kasyful (Universitas Islam Negeri Ar-Raniry, 2022)
SMP IT Madrasatul Quran is one of the Islamic boarding schools that offer Arabic as a second language programs in the everyday school environment. This also includes memorizing verses of the Qur'an and studying Arabic for eighteen hours a week at school. They also learn to speak and understand Arabic scripts. This process is a good effort to improve students' ability and understanding of Arabic texts. But in reality, most of the students face difficulty in understanding the Arabic language, especially in understanding the text because they find it difficult to memorize the vocabulary and they have a lack of vocabulary, and this makes them weak in understanding and speaking the Arabic language. Therefore, the researcher wanted to conduct a research entitled: